Suffering it Out: Meeting the Needs of Health Care Delivery in a Rural Area - Kathleen Huttlinger; Jennifer Schaller-Ayers; Tony Lawson; James Ayers (Rural Nurse Organization; Binghamton University, 2003)
The health status of the people in the coal-producing counties of southwest Virginia is poor despite an apparent high provider to population threshold. This study used a qualitative approach to obtain information about accessibility to health care services and about perceptions of personal health status. Interview and focus group data revealed that the delivery of health care services is compromised by poverty and the large number of medically underinsured and uninsured individuals. Emergent themes included "suffering it out," a strong sense of community, quality time with provider and needed fixes. Another significant finding revealed the need for specialty providers. Community health nurses can provide a valuable service by making people aware of free and low cost prevention and prescription assistance programs, assist with understanding government health forms, and locating other low-cost health services for clients in their districts.